2008
DOI: 10.1590/s0100-29452008000300005
|View full text |Cite
|
Sign up to set email alerts
|

Quantificação de clorofilas em folhas de macieiras 'Royal Gala' e 'Fuji' com métodos ópticos não-destrutivos

Abstract: O método-padrão para a quantificação de clorofilas em folhas é destrutivo e relativamente demorado. Com o advento dos medidores portáteis, a quantificação de clorofilas tornou-se fácil e rápida, podendo ser realizada de forma não-destrutiva a campo. Colorímetros também podem ser utilizados para a avaliação não-destrutiva da coloração de tecidos vegetais, e, portanto, para a quantificação de clorofilas em folhas. Este trabalho foi conduzido visando a avaliar a viabilidade de utilização de um colorímetro, como a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
5
0
5
Order By: Relevance
“…The SPAD (Soil Plant Analysis Diagnostic) chlorophyll meter is a portable, user-friendly, effective, and nondestructive device that can be used to estimate the nitrogen status of plants ( RUBIO-COVARRUBIAS et al, 2009;DIAS et al, 2012) and the chlorophyll content in leaves. The SPAD index has been used since the 1990s in studies on the quantification of leaf chlorophyll (AMARANTE et al, 2008; JESUS; MARENCO, 2008), plant nutrition (VALE; PRADO, 2009;SIMÕES et al, 2010;PINOCHET, 2010;SANTOS et al, 2011;DIAS et al, 2012;NAVA;CIOTTA, 2013;RAMOS et al, 2013), yield estimates (GIL et al, 2002), evaluation of scion/ rootstock combinations (ZARROUK et al, 2006a;PICOLLOTO et al, 2012), and translocated graft incompatibility, because low SPAD index values may be associated with the blockage of carbohydrate assimilation and nitrogen uptake (ZARROUK et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…The SPAD (Soil Plant Analysis Diagnostic) chlorophyll meter is a portable, user-friendly, effective, and nondestructive device that can be used to estimate the nitrogen status of plants ( RUBIO-COVARRUBIAS et al, 2009;DIAS et al, 2012) and the chlorophyll content in leaves. The SPAD index has been used since the 1990s in studies on the quantification of leaf chlorophyll (AMARANTE et al, 2008; JESUS; MARENCO, 2008), plant nutrition (VALE; PRADO, 2009;SIMÕES et al, 2010;PINOCHET, 2010;SANTOS et al, 2011;DIAS et al, 2012;NAVA;CIOTTA, 2013;RAMOS et al, 2013), yield estimates (GIL et al, 2002), evaluation of scion/ rootstock combinations (ZARROUK et al, 2006a;PICOLLOTO et al, 2012), and translocated graft incompatibility, because low SPAD index values may be associated with the blockage of carbohydrate assimilation and nitrogen uptake (ZARROUK et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, both Amarante et al (2008), using apple, and Richardson et al (2002), using Betula papyrifera, reported that the SPAD-502 estimate of chlorophyll b was less reliable than the estimates of chlorophyll a and the total chlorophyll content. According to Neves et al (2005), these results may be explained by the fact that the absorption peak of chlorophyll a is similar to the wavelength emitted by the device and, thus, more difficult to separate.…”
Section: Resultsmentioning
confidence: 99%
“…Agronomy Maringá, v. 34, n. 3, p. 325-329, July-Sept., 2012 (ARGENTA et al, 2001), apple (AMARANTE et al, 2008), and tomato (SCHUELTER et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…No entanto, em estudo de Amarante et al (2008), para a quantificação de clorofilas em folhas de macieiras utilizando métodos ópticos não destrutivos em ambas as bases de referência (área foliar e massa fresca das folhas), os autores obtiveram modelos ajustados pelo índice SPAD, com diferenças expressivas de R 2 entre clorofilas a e total, e a clorofila b. Segundo esses autores, métodos não destrutivos ópticos são melhores para a estimativa dos teores de clorofilas a e total do que de clorofila b, em macieiras. Segundo Neves et al (2005), isto ocorre tendo em vista que o pico de absorção na faixa vermelha do espectro pela clorofila a (663 nm), além de ser maior que o da clorofila b, está muito próximo do comprimento de onda emitido pelo SPAD-502 (650 nm).…”
Section: Resultsunclassified
“…Com o advento dos medidores portáteis, que utilizam princípios ópticos não destrutivos, baseados na absorbância e/ou refletância da luz pelas folhas, a determinação de clorofilas tornou-se fácil e rápida, podendo ser realizada a campo (RICHARDSON, DUIGAN, BERLYN, 2002;AMARANTE et al, 2008). Neste sentido, a determinação do teor relativo de clorofila, por meio do clorofilômetro SPAD, tem surgido como um método alternativo aos procedimentos convencionais destrutivos (SALLA; RODRIGUES; MARENCO, 2007).…”
Section: Introductionunclassified